2018
DOI: 10.1039/c8cc07921h
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's amyloid-beta intermediates generated using polymer-nanodiscs

Abstract: Polymethacrylate-copolymer (PMA) encased lipid-nanodiscs (~10 nm) and macro-nanodiscs (>15 nm) are used to study Aβ1–40 aggregation. We demonstrate that PMA-nanodiscs form a ternary association with Aβ and regulate its aggregation kinetics by trapping intermediates. Results demonstrating reduced neurotoxicity of nanodisc-bound Aβ oligomers are also reported.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 25 publications
2
66
0
Order By: Relevance
“…As another benefit, the polymer-based nanodiscs lack spectroscopic signals that overlap with those of the protein of interest. This nanodisc technology was previously applied to the analysis of the oligomer formation by amyloidogenic peptides such as human islet amyloid polypeptide [ 7 ] and amyloid-β peptide [ 8 ] in the membrane.…”
Section: Artificial Membrane Systems That Simulate the Environment Ofmentioning
confidence: 99%
“…As another benefit, the polymer-based nanodiscs lack spectroscopic signals that overlap with those of the protein of interest. This nanodisc technology was previously applied to the analysis of the oligomer formation by amyloidogenic peptides such as human islet amyloid polypeptide [ 7 ] and amyloid-β peptide [ 8 ] in the membrane.…”
Section: Artificial Membrane Systems That Simulate the Environment Ofmentioning
confidence: 99%
“…Some amyloid oligomeric conformers were more toxic than amyloid fibrils [ 37 , 38 , 39 ]. Different oligomers showed different structures and toxicities [ 40 , 41 ]. Thus, amyloid fibrils with different structures may reflect variable toxicity, aggregation pathways, and surrounding microenvironments in different patients and symptoms [ 1 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray crystallography demonstrated the fibril structures of amyloidogenic protein fragments [ 43 , 44 ] and oligomers of Aβ peptides [ 45 , 46 , 47 , 48 ]. NMR studies reported the high-resolution structural details of membrane-bound amyloid oligomers [ 41 , 49 , 50 ]. Solution- and solid-state NMR was used to investigate the monomer and transient intermediate structures in Aβ assemblies [ 16 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleation theory is widely applied to direct the crystallization of small molecule polymorphs, and nucleation driven control over amyloid structure has been used to 5 produce fibrils of sufficient purity for X-ray crystallography and solid-state NMR spectroscopy through repeated seeding (17,39). In addition to amyloid seeds, prior work has shown that exogenous materials, including nanoparticles, polymers, and small molecules can act as nucleants that influence the kinetics of amyloid aggregation (40)(41)(42)(43)(44). While the effect of these agents on the kinetics of amyloid formation has been widely studied, it is generally unclear how changing aggregation conditions dictates the structure of the resulting amyloid fibrils.…”
Section: Introductionmentioning
confidence: 99%